Eksplorasi Pemanfaatan Aplikasi Quizizz sebagai Media Evaluatif dalam Pembelajaran Bahasa Arab - Izzan, Fadhil (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study investigates the effectiveness of the Quizizz application as an evaluative tool in Arabic language learning at MAN 2 Mataram. Employing a quantitative approach with a quasi-experimental pretest–posttest control group design, the research involved 120 students assigned to experimental and control groups. Research instruments consisted of an Arabic comprehension test, an ARCS-based learning motivation questionnaire, and observation sheets. The findings indicate that the integration of Quizizz significantly improved students’ answer accuracy by 17.8 percentage points, compared to only a 3.1-point increase in the control group. The experimental group also recorded a gain score of 15.3 with a very large effect size (d = 1.63). Furthermore, students’ learning motivation increased across all ARCS dimensions, with the most substantial improvement observed in the satisfaction component. Gamification features, immediate feedback, and the platform’s self-paced learning system were found to contribute to enhanced learning outcomes and student motivation. However, the study also identified challenges such as limited internet access and varying levels of technological proficiency among students. Overall, the results demonstrate that Quizizz is an effective and innovative evaluative medium for Arabic language instruction.